CYSTATIN S AS A MARKER OF CYCLOSPORINE A RENAL TOXICITY IN CHILDREN WITH NEPHROTIC SYNDROME - O.V. Komarova; M.V. Rozhkova; A.N. Tsygin; A.G. Kucherenko; I.E. Smirnov; L.V. Leonova ("Paediatrician" Publishers LLC, 2010)
The use of cystatin С as a probable marker of renal toxicity of cyclosporine A in children with nephritic syndrome, treated with this medication for a long time, is the subject of an interest. The present study included 29 children treated with cyclosporine A, divided into 3 groups depending on the duration of treatment (< 1 year, 1-2 years and > 2 years). The increase of cystatin С level in these groups compared with cystatin С level in control group (10 children without diseases of kidney) was marked. The highest level of cystatin С was detected in children treated with therapeutic doses of cyclosporine A (3-5 mg/kg daily) over 1 year. Authors showed positive correlation between cystatin С level in serum and medication's dose.Key words: children, nephritic syndrome, cystatin С, cyclosporine A.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):131-135)